The essentials of computer organization and architecture - Null, Linda (Jones & Bartlett Learning, 2024)
"The Essentials of Computer Organization and Architecture focuses on the function and design of the various components necessary to process information digitally. This title presents computing systems as a series of layers, taking a bottom-up approach by starting with low-level hardware and progressing to higher-level software"--